THE ROLE OF SELF-CONCEPT ON CHILDREN'S ASSERTIVE BEHAVIOR IN THE SPECIAL GUIDANCE FOR CHILDREN CLASS 1 KUTOARJO - Binta Nur ‘Izzatie; Qisthina Aulia (Polteknik Ilmu Pemasyarakatan, 2021)
This study aims to determine the role of self-concept in children on assertive behavior. Sampling was done by purposive technique in LPKA Kelas 1 Kutoarjo for 43 children. The instruments of this study are self-concept scale that based on the Tennese Self-Concept Scale developed by Fitts (1965) and the assertive behavior scale using the Rathus Assertiveness developed by Rathus (1973). Through simple linear regression analysis, it is known that self-concept play role in children's assertive behavior by 70,9% (p < .05). The results of the study also showed that the internal dimension had greater influence (71,2%) than the external dimension (67,1%) of the self-concept on assertive behavior. This study is expected to be one of the considerated by LPKA to assist children in developing positive self-concepts to increase assertive behavior.